The role of State Official Wealth Report in realizing the principles of Maqashid Sharia - Nuryanto, Ahmad Dwi; Jaelani, Abdul Kadir (Legality : Jurnal Ilmiah Hukum, 2024)
This research aims to examine and analyze problems related to the implementation of maqasid sharia principles in effective reporting of state administrators' assets in Indonesia and to look for factors causing the ineffectiveness of legal instruments for reporting state administrators' assets in realizing the general principles of government in Indonesia. This research employed a normative legal method, with its prescriptive and applied nature. The research results show that, first, the implementation of maqasid sharia principles in reporting the assets of state administrators is in line with Hifz al-din (maintaining religion), Hifz an-nafs (maintaining the soul), Hifz al-aql (maintaining reason), Hifz an-nasl (maintaining offspring), and Hifz al-mal (maintaining assets); however, the challenge of implementing the principles of maqasid sharia in regulating the reporting of state administrators' assets requires a strong commitment from legal institutions, government, and society. Second, the factor causing the ineffectiveness of the legal instrument for reporting state administrators' assets still needs to be a more vital law enforcement factor. This can be seen in the LHKPN reporting instrument, which is the responsibility of the Corruption Eradication Commission. To deal with these problems, a legal instrument for reporting state administrators' assets is needed to embody the General Principles of Good Governance in Indonesia based on eight principles that the law must fulfil as a basis for forming reasonable regulations.